1986
DOI: 10.1007/bf02412112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D-Met2, Pro5-enkephalinamide on pain tolerance and some cognitive functions in man

Abstract: The effects of D-Met2, Pro5-enkephalinamide (EA) on pain tolerance and some cognitive functions have been examined in healthy male volunteers. Dihydrocodeine (DC) was used as reference substance. Applying the submaximum effort tourniquet technique EA (10 mg SC) was found to elevate the pain threshold similarly to DC (20 mg SC). Neither DC nor EA impaired the performance in the symbol cancellation test, which quantitates the intensity of attention. In this assay rather a slight improvement was detected. in addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Dihydrocodeine had no effect on a test of memory (the forward and backward digit span test) in healthy volunteers (Szekely et al, 1986). Furthermore, dihydrocodeine did not impair performance on a word fluency test (Guilford, 1967) that required participants to recall information from the distant past.…”
Section: Effects Of Opioids On Psychomotor and Cognitive Functioningmentioning
confidence: 94%
See 1 more Smart Citation
“…Dihydrocodeine had no effect on a test of memory (the forward and backward digit span test) in healthy volunteers (Szekely et al, 1986). Furthermore, dihydrocodeine did not impair performance on a word fluency test (Guilford, 1967) that required participants to recall information from the distant past.…”
Section: Effects Of Opioids On Psychomotor and Cognitive Functioningmentioning
confidence: 94%
“…Szekely, Torok, Karczag, Tolna, and Till (1986) found that dihydrocodeine did not impair performance on a 5-min symbol-cancellation test (Le Toulouse, Vaschide, & Pieron, 1904) that is similar to the DSST. Participants were given dihydrocodeine and were then asked to cross out three target symbols in 29 lines of eight symbols.…”
Section: Effects Of Opioids On Psychomotor and Cognitive Functioningmentioning
confidence: 98%
“…Across a wide variety of dosages and drugs, most studies did not observe an effect of opioid agonists and antagonists on working memory (see Table 3). Three studies did observe effect on working memory (Ghoneim, Mewaldt, & Thatcher, 1975;Martín del Campo, McMurray, Besser, & Grossman, 1992;Székely, Török, Karczag, Tolna, & Till, 1986). However, since these findings were in opposite directions and the studies used limited samples (8 or 10 males per study), it is difficult to draw firm conclusions about these results.…”
Section: Coding Taskmentioning
confidence: 95%
“…Interestingly, across a wide variety of doses and drugs in 16 studies, opioid agonists and antagonists typically do not affect working memory performance (Table 3). Three studies did observe effects on working memory (Ghoneim, Mewaldt, & Thatcher, 1975; Martín del Campo, McMurray, Besser, & Grossman, 1992; Székely, Török, Karczag, Tolna, & Till, 1986) but showed findings in opposite directions and had small study samples (8 or 10 males per study).…”
Section: Review Of Studies On Cognitive Controlmentioning
confidence: 99%